2013
DOI: 10.1021/ic402556g
|View full text |Cite
|
Sign up to set email alerts
|

Cage Shrinkage of Fullerene via a C2 Loss: from IPR C90(28)Cl24 to Nonclassical, Heptagon-Containing C88Cl22/24

Abstract: A new case of chlorination-promoted fullerene cage shrinkage is reported. Chlorination of C90 (isolated pentagon rule isomer no. 28) with VCl4 afforded C88Cl22 with a nonclassic carbon cage (NCC) containing 1 heptagon and 13 pentagons including 2 fused pairs flanking the heptagon. The pathway of C2 abstraction from the C90 cage is suggested on the basis of density functional theory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 17 publications
2
53
0
3
Order By: Relevance
“…Later, chlorination‐promoted C 2 loss reactions (C2Ls) below 400 °C were reported for several higher fullerenes 7. A single C 2 loss in the course of chlorination of C 86 (16) and C 90 (28) (isomer numbering in parentheses is according to the spiral algorithm1) yielded NC fullerene chlorides C 84 ( NC 1)Cl 32 7a and C 88 ( NC 1)Cl 22 ,7b respectively (the numeral after NC indicates the number of heptagons in the carbon cage). In C 96 , both single and double C 2 losses have been reported that gave, respectively, C 94 ( NC 1)Cl 28 and C 92 ( NC 2)Cl 32 7c.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Later, chlorination‐promoted C 2 loss reactions (C2Ls) below 400 °C were reported for several higher fullerenes 7. A single C 2 loss in the course of chlorination of C 86 (16) and C 90 (28) (isomer numbering in parentheses is according to the spiral algorithm1) yielded NC fullerene chlorides C 84 ( NC 1)Cl 32 7a and C 88 ( NC 1)Cl 22 ,7b respectively (the numeral after NC indicates the number of heptagons in the carbon cage). In C 96 , both single and double C 2 losses have been reported that gave, respectively, C 94 ( NC 1)Cl 28 and C 92 ( NC 2)Cl 32 7c.…”
mentioning
confidence: 99%
“…In ref. 7b, certain mechanistic considerations have been presented regarding C 2 elimination in the chlorinated form. Without chlorination, pyrolytic degradation of higher fullerenes such as C 76 , C 78 , and C 84 into C 60 and C 70 is known to proceed only above 1000 °C8 and no clear mechanism has been suggested so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly accepted explanation for the existence of non-classical fullerenes involves a combination of the following: (a) those fullerenes with a lower number of pentagon-pentagon bonds are usually more stable than those with a higher number of pentagon-pentagon bonds -this is known as the pentagon adjacent penalty rule (PAPR) [3][4][5]; (b) in fullerenes composed of squares and hexagons, it is energetically favorable when all squares are surrounded by hexagons -this is known as the isolated-square rule (ISR) [6,7]; (c) those isomers with a lower number of square-square bonds have an energetic advantage over those with a higher number of square-square bonds -this is known as the square adjacency penalty rule (SAPR) [8]. Recently, both from the experimental and the theoretical sides, the study of non-classical fullerenes has been attracting increasing interest [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Several theoretical calculations have been performed to establisht he relative stability of C 90 isomers and estimate their relative populations in the experimental mixtures.…”
mentioning
confidence: 99%